Discovery of 5-methyl-N-(2-arylquinazolin-7-yl)isoxazole-4-carboxamide analogues as highly selective FLT3 inhibitors - Daseul Im; Hyungwoo Moon; Jinwoong Kim; Youri Oh; Miyoung Jang; Jung-Mi Hah (Taylor & Francis Group, 2020)
A series of 4-arylamido 5-methylisoxazole derivatives with quinazoline core was designed and synthesised based on conformational rigidification of a previous type II FMS inhibitor. Most of quinazoline analogues displayed activity against FLT3 and FLT3-ITD. Compound 7d, 5-methyl-N-(2-(3-(4-methylpiperazin-1-yl)-5-(trifluoromethyl)phenyl)quinazolin-7-yl)isoxazole-4-carboxamide, exhibited the most potent inhibitory activity against FLT3 (IC50= 106 nM) with excellent selectivity profiles over 36 other protein kinases including cKit and FMS kinase. Compound 7d was also active in FLT-ITD, with an IC50 value of 301 nM, and other FLT3 mutants showing potential as an AML therapeutics.